The Reflection of Marxist Feminism in Suzanne Collins’s Mockingjay - NAILAH, NAILAH (LANTERN (Journal on English Language, Culture and Literature), 2016)
this journal analyzes Marxist feminism, domination, alienation, class struggle, and revolution that exist in novel Mockingjay, especially in regards to Katniss Everdeen as the main character. This character is so interesting to be analyzed because the character represents the idea of Marxist feminism. The main purpose of this journal is to understand more about Marxist feminism in Mockingjay. This journal uses sociological approach. The theory used in this study is Marxist feminism. The result of this study is the analysis of intrinsic elements and extrinsic elements of prose. There are some intrinsic elements discussed in this thesis, such as character, setting, conflict and allegory. Moreover, the extrinsic element is the analysis of Katniss Everdeen as the main character in novel Mockingjay who represents the effort of Marxist feminism. It provides a description of domination, alienation, class struggle, and Marxist feminism. In conclusion, this thesis provides a discussion about Marxist feminism and its process, especially in regards to Katniss Everdeen as the main character.